2011
DOI: 10.1074/jbc.m110.169821
|View full text |Cite
|
Sign up to set email alerts
|

ErbB2 Stabilizes Epidermal Growth Factor Receptor (EGFR) Expression via Erk and Sprouty2 in Extracellular Matrix-detached Cells

Abstract: Epithelial cells are dependent on extracellular matrix (ECM) attachment for maintenance of metabolic activity and suppression of apoptosis. Here we show that loss of ECM attachment causes down-regulation of epidermal growth factor receptor (EGFR) and ␤1 integrin protein and mRNA expression and that ErbB2, which is amplified in 25% of breast tumors, reverses these effects of ECM deprivation. ErbB2 rescue of ␤1 integrin mRNA and protein in suspended cells is dependent on EGFR, however, the rescue of EGFR express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 68 publications
2
47
0
Order By: Relevance
“…4F,G; Grassian et al 2011). This is consistent with a previous report showing that glucose uptake is insensitive to Mek inhibition (Lazar et al 1995).…”
Section: Erk Signaling Regulates Pyruvate Metabolismsupporting
confidence: 82%
See 3 more Smart Citations
“…4F,G; Grassian et al 2011). This is consistent with a previous report showing that glucose uptake is insensitive to Mek inhibition (Lazar et al 1995).…”
Section: Erk Signaling Regulates Pyruvate Metabolismsupporting
confidence: 82%
“…S3F), suggesting that the ErbB2 regulation of PDK4 is independent of PI3K/Akt signaling. ErbB2 also maintains activation of the Mek/Erk pathway in ECMdetached cells (Reginato et al 2003;Schafer et al 2009;Grassian et al 2011), and treatment of MCF-10A ErbB2 cells with either of two Mek inhibitors (UO126 and PD98059) increased PDK4 mRNA and protein levels under ECMdetached conditions (Figs. 3A,B; Supplemental Fig.…”
Section: Pdk4 Expression Is Regulated By Ecm Attachment and Erkmentioning
confidence: 99%
See 2 more Smart Citations
“…[18][19][20] Interestingly, previous studies have shown that ErbB2 and EGFR, which are hyperactivated in a substantial percentage of IBC patients, 21 can effectively antagonize the anoikis program to facilitate anchorage-independent growth. [22][23][24][25][26][27][28] However, a detailed examination of the molecular mechanisms underlying anoikis inhibition in IBC cells has yet to be completed. In this study, we demonstrate that signaling from EGFR and ErbB2 through ERK/MAPK has a major role in the ability of IBC cells to survive in the absence of ECM attachment.…”
mentioning
confidence: 99%